2003
DOI: 10.1080/0269905021000010122
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury and violent crime

Abstract: Published epidemiological data regarding TBI may underestimate the prevalence in urban populations, which may have confounded earlier studies of TBI and domestic violence. The reported prevalence in this sample of defendants suggests implications for the justice system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 8 publications
0
46
1
Order By: Relevance
“…Most adults, at some point in their lives, experience a bump on the head, but never experience adverse psychological or behavioral changes from the injury; though for some, TBI can result in impairments in brain functioning that can affect decision making and social skills (Ferguson, Pickelsimer, Corrigan, Bogner, & Wald, 2012). Unless these individuals are identified early on, and diverted into appropriate treatment programs, the TBI can lead to a host of negative outcomes such as attention problems, increased aggression, hypersexual behavior, and a lack of impulse control, all of which are particularly salient if the injury occurs during childhood (Eghwrudjakpor & Essien, 2008;Fazel, Lichtenstein, Grann, & Langstrom, 2011;Leon-Carrion, Javier, & Ramos, 2003;Turkstra, Jones, & Toler, 2003).…”
Section: Traumatic Brain Injury and Recidivism Among Returning Inmatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most adults, at some point in their lives, experience a bump on the head, but never experience adverse psychological or behavioral changes from the injury; though for some, TBI can result in impairments in brain functioning that can affect decision making and social skills (Ferguson, Pickelsimer, Corrigan, Bogner, & Wald, 2012). Unless these individuals are identified early on, and diverted into appropriate treatment programs, the TBI can lead to a host of negative outcomes such as attention problems, increased aggression, hypersexual behavior, and a lack of impulse control, all of which are particularly salient if the injury occurs during childhood (Eghwrudjakpor & Essien, 2008;Fazel, Lichtenstein, Grann, & Langstrom, 2011;Leon-Carrion, Javier, & Ramos, 2003;Turkstra, Jones, & Toler, 2003).…”
Section: Traumatic Brain Injury and Recidivism Among Returning Inmatesmentioning
confidence: 99%
“…However, many of these studies have targeted specific populations-homicide offenders (Blake, Pincus, & Buckner, 1995;Freedman & Hemenway, 2000;Lewis, Pincus, Feldman, Jackson, & Bard, 1986), sex offenders (Langevin, 2006), or those with mental health or a substance abuse problem (DelBello, et al, 1999;Hawley & Maden, 2003;Martell, 1992;Walker, Staton, & Leukefeld, 2001)-rather than the general offender population. Moreover, sampling strategies have varied considerably with most relying on convenience samples (Blake, et al, 1995;DelBello, et al, 1999;Diamond, Harzke, Magaletta, Cummins, & Frankowski, 2007;Freedman & Hemenway, 2000;Lewis, et al, 1986;Turkstra, et al, 2003;Williams, Cordan, Mewse, Tonks, & Burgess, 2010).…”
Section: Traumatic Brain Injury and Criminal Behaviormentioning
confidence: 99%
“…For example, in one sample of 20 healthy African-American males with an average age of 32.6 years and an average of 12.7 years of education assessed with a questionnaire, 60% reported a history of TBI [7]. In contrast, using a large cross-sectional community sample and operationalizing TBI as having had a serious head injury with resultant loss of consciousness of 15 min or more, Butterworth et al [8] found a TBI prevalence of only 5.7% in 7,488 subjects.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant portion of TBI research using incarcerated samples has focused specifically on TBI as it relates to violent criminal behavior. Researchers have explored possible links between TBI and domestic violence (Rosenbaum et al, 1994;Turkstra, Jones, & Toler, 2003;Marsh & Martinovich, 2006), murder (Lewis et al, 1986), and mixed violent offenses (Leon-Carrion & Ramos, 2003;Brewer-Smyth, Burgess, & Shults, 2004).…”
Section: Implications Of Tbi In Offender Populationsmentioning
confidence: 99%
“…Some researchers created their own classification system to describe injury severity (Hawley & Maden, 2003: Turkstra et al, 2003 while others did not report severity levels (Sarapata et al, 1998;Brewer-Smyth et al, 2004). Very few studies were found to have used the CDC, ACRM, or WHO definitions of TBI described above (e.g., Diamond et al, 2007;Schofield et al, 2006;Slaughter et al, 2003).…”
Section: Traumatic Brain Injury (Tbi) Is a Significant Public Health mentioning
confidence: 99%